Holistic Parenting and Social Media Parenting Content on Parental Self Efficacy and Knowledge - Anisa, Nur; Inayatur Robbaniyah; Retno Tri Wulandari; Tomas Iriyanto; Ahmad Samawi (Jurnal Pendidikan Anak Usia Dini Undiksha, 2022)
Handling cases of violence against children requires the cooperation of various parties, academics, practitioners and the community. Currently, much parenting content is emerging from the community on social media. This study examines the effect of parents' perceptions of holistic parenting training and social media parenting content on parents' self-efficacy and their effect on parental knowledge. This research belongs to the type of explanatory research. The population in this study was 87 parents because the sample size was <100, so the sampling technique used was total sampling involving all members of the population. Data collection in the study was carried out using the non-test method, with a research instrument in the form of a Likert scale instrument. The data obtained in the study were then analyzed using a structural Equation Model (SEM) approach with the help of the smart PLS application. The research was conducted through validity and reliability testing, the R Square Test, and deep model analysis. The research analysis results show that holistic parenting and social media parenting content affect parental self-efficacy and parenting knowledge (H1, H2, H4 and H5 are accepted), and parent self-efficacy can influence parenting knowledge (H3 is accepted). Meanwhile, Parent Self Efficacy can mediate holistic parenting relationships and social media parenting content on parenting knowledge (H6 and H7 are accepted). These results show that holistic parenting style and social media content significantly affect self-efficacy and parental knowledge.